2022
DOI: 10.1177/08948453211070027
|View full text |Cite
|
Sign up to set email alerts
|

Examining Differentiation of Self Within Career Construction Model of Adaptation

Abstract: The present study examined the role of differentiation of self (DoS) in the career construction model of adaptation (CCMA) using a total sample of 243 married adults. Specifically, career construction theory (CCT) was extended by integrating Bowen family systems theory (BFST) and incorporating DoS as an adaptivity construct into the model. The data displayed a good fit to the model, and all hypothesized associations were supported. The direct paths from DoS to career adaptability, job, life, and marital satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
0
1
Order By: Relevance
“…Previous research has indicated that higher DoS predicts higher career adaptability in the context of healthy family functioning (Fiorini & Patta Bardagi, 2018). For instance, married Turkish couples with higher DoS reported higher career adaptability (Akün et al, 2023). However, we found a negative relationship between DoS and career adaptability, contrary to our first hypothesis.…”
Section: Dos To Career Adaptability (Hypothesis 1)contrasting
confidence: 99%
“…Previous research has indicated that higher DoS predicts higher career adaptability in the context of healthy family functioning (Fiorini & Patta Bardagi, 2018). For instance, married Turkish couples with higher DoS reported higher career adaptability (Akün et al, 2023). However, we found a negative relationship between DoS and career adaptability, contrary to our first hypothesis.…”
Section: Dos To Career Adaptability (Hypothesis 1)contrasting
confidence: 99%